Advancing Culture of Living with Landslides: Volume 1 ISDR-ICL Sendai Partnerships 2015-2025 - Matjaž Mikoš (WLF: Workshop on World Landslide Forum, 2017)
This volume contains peer-reviewed papers from the Fourth World Landslide Forum organized by the International Consortium on Landslides (ICL), the Global Promotion Committee of the International Programme on Landslides (IPL), University of Ljubljana (UL) and Geological Survey of Slovenia in Ljubljana, Slovenia from May 29 to June 2, 2017. The complete collection of papers from the Forum is published in five full-color volumes.